Do no harm [large type] - Collins, Max Allan (Collins, Max Allan. Memoirs of Nathan Heller., 2020)
"It's 1954 and Heller takes on the Sam Sheppard case--a young doctor is startled from sleep and discovers his wife brutally murdered. He claims that a mysterious intruder killed his wife. But all the evidence points to a disturbed husband who has grown tired of married life and yearned to be free at all costs. Sheppard is swiftly convicted and sent to rot in prison. Just how firm was the evidence...and was it tampered with to fit a convenient narrative to settle scores and push political agendas? Nathan's old friend Eliot Ness calls in a favor and as Nathan digs into the case he becomes convinced of Sheppard's innocence. But Nate can't prove it and has to let the case drop. The road to justice is sometimes a long one. Heller's given another chance years later and this time he's determined to free the man...even if it brings his own death a bit closer"--